2001
DOI: 10.1074/jbc.m100788200
|View full text |Cite
|
Sign up to set email alerts
|

“Weak Toxin” from Naja kaouthia Is a Nontoxic Antagonist of α7 and Muscle-type Nicotinic Acetylcholine Receptors

Abstract: A novel "weak toxin" (WTX) from Naja kaouthia snake venom competes with [125 I]␣-bungarotoxin for binding to the membrane-bound Torpedo californica acetylcholine receptor (AChR), with an IC 50 of ϳ2.2 M. In this respect, it is ϳ300 times less potent than neurotoxin II from Naja oxiana and ␣-cobratoxin from N. kaouthia, representing short-type and long-type ␣-neurotoxins, respectively. WTX and ␣-cobratoxin displaced [125 I]␣-bungarotoxin from the Escherichia coli-expressed fusion protein containing the rat ␣7 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 39 publications
8
92
2
Order By: Relevance
“…One such toxin, candoxin from Bungarus candidus, blocks both the muscle and ␣7 nAChRs with nanomolar affinity (35), whereas another non-conventional toxin, weak toxin from the cobra Naja kaouthia, acts on these receptors only with micromolar affinity (36). Thus, ws-LYNX1 in terms of affinities for nAChRs is close to weak toxin, but this toxin still shows virtual irreversibility of action (36). Interestingly, a common feature of ws-LYNX1 and weak toxin is their action on muscarinic acetylcholine receptors (3, 37).…”
Section: Discussionmentioning
confidence: 99%
“…One such toxin, candoxin from Bungarus candidus, blocks both the muscle and ␣7 nAChRs with nanomolar affinity (35), whereas another non-conventional toxin, weak toxin from the cobra Naja kaouthia, acts on these receptors only with micromolar affinity (36). Thus, ws-LYNX1 in terms of affinities for nAChRs is close to weak toxin, but this toxin still shows virtual irreversibility of action (36). Interestingly, a common feature of ws-LYNX1 and weak toxin is their action on muscarinic acetylcholine receptors (3, 37).…”
Section: Discussionmentioning
confidence: 99%
“…However, electrophysiological studies have revealed that a -bungarotoxin (IC 50 approximately 5 nM) produced an irreversible block of muscle (a 1) 2 b1gd receptors (68), whereas candoxin (IC 50 approximately 10 nM) produced a reversible blockade of the same receptor (58). Furthermore, WTX (Naja kaouthia), a non-conventional toxin that is structurally similar to candoxin but a 1000-fold weaker antagonist of muscle nAChRs, is almost irreversible in its action (54). Therefore, the reversibility of a -neurotoxin action at the neuromuscular junction is not always a reflection of their binding affinity to the receptor and may perhaps be associated with a specific area of interaction on the toxin molecule, distinct from the receptor recognition site (67).…”
Section: Pharmacology Of Three-finger A-neurotoxinsmentioning
confidence: 99%
“…Short-chain a -neurotoxins as well as atypical longchain toxins (Lc-a and Lc-b from Laticauda colubrina), which lack this fifth disulfide bridge and non-conventional toxins WTX (Naja kaouthia) and Wntx-5 (Naja sputatrix), both of which have the fifth disulfide bridge in loop I and lack the loop II helical conformation, have weak affinity, in micromolar concentrations (K d approximately 3 -22 mM) at best, for the neuronal a 7 nAChR (50,54,56). Interestingly, candoxin (Bungarus candidus) is the first known toxin that lacks this critical helix-like conformation cyclized by the fifth disulfide bridge in loop II and yet blocks neuronal a 7 nAChRs in low nanomolar concentrations (58).…”
Section: Conformational Determinants Of Structure-function Of A-nmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only two proteins with this disulfide bridge scaffold have been structurally characterized. They are bucandin (pdb: 1F94 (X-ray) and 1IJC (NMR)), another toxin from Bungarus candidus venom [35][36] and Cd59 (pdb: 1CDQ), which is a cell surface protein 37 .…”
Section: Issn 1424-6376 Page 12mentioning
confidence: 99%